Preparation and Structural Identification of Peptides Stimulating Cholecystokinin Secretion from the Skin of Puffer Fish - SONG Hongdong, REN Shaoxia, SHAO Zhuwei, GE Shaocheng, QIAO Kun, LIU Zhiyu (Shipin Kexue, 2025)
To obtain collagen peptides with the ability to stimulate cholecystokinin (CCK) secretion, collagen was extracted from puffer fish skin and hydrolyzed with alkaline protease. The CCK secretion-promoting activity of collagen peptides with different hydrolysis degrees was evaluated using an in vitro enteroendocrine STC-1 cell model. The results showed that the peptide with a hydrolysis degree of 12% had the highest CCK secretion-promoting activity. This peptide was separated and purified using a YMC ODS C18 column. Six peptide sequences were identified using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Among them, three peptides, LSGK, LPGKPGL and KMTPT, had significant CCK secretion-promoting activity. This study provides a theoretical basis for the application of puffer fish skin peptides in regulating intestinal CCK secretion and provides new ideas for the development of functional products based on puffer fish skin peptides.